IMPLEMENTASI ANALISIS FAKTOR DALAM MENGANALISIS KEPUASAN NASABAH TERHADAP KUALITAS LAYANAN (STUDI KASUS: LPD SIDAKARYA) - YASA, I PUTU ARISTA; SUCIPTAWATI, NI LUH PUTU; SUSILAWATI, MADE (E-Jurnal Matematika; Vol 6 No 2 (2017)DO - 10.24843/MTK.2017.v06.i02.p160, 2017)
The aim of this study was to be able to determine some factors that affected customer satisfaction on the quality of the services provided by LPD Sidakarya . Samples of this study were 150 respondents. The respondents were customers of LPD Sidakarya who have been registered since at least a year ago. There were two variables in this study; i.e. perception and expectation variables in which each of the variable had 30 indicators that affected the satisfaction of the customer on service quality. In addition, this study also determined five factors that affected customer satisfaction on the service quality. The method used was confirmatory factor analysis. It was found on the results of this study that the formed factor of these 30 indicators that affected the satisfaction of the customer on service quality indeed five main factors consisted of tangibles, reliability, responsiveness, assurance and empathy. The most dominant factor obtained was reliability.